Magnetic measurement of nanocrystalline alloy based on a single sheet tester. Issue 1 (20th December 2020) - Zhang, Xiwei; Li, Lin; Zhang, Yan; Pang, Jian
Abstract: Generally, for the measurement of magnetic characteristics of nanocrystalline alloy, the magnetic circuit length ( l m ) is assumed as a constant, and magnetic measurement under square waveform is rarely focused. This paper examines that magnetic characteristics of nanocrystalline alloy are measured under sinusoidal waveforms and square waveforms based on a single sheet tester. The factors related to l m are analysed from the tested data under sinusoidal excitations, and a novel method to determine l m is presented, which is then extended to the case under square waveforms. By combining with a power electronic inverter, the influence of power electronic topology on measurements is analysed, and the oscillation mechanism of excitation current of single sheet tester is revealed. As a result, the limitation of the H‐coil method for acquiring the magnetic field intensity H under square waveforms is pointed out, and improved magnetic circuit method is introduced. It is shown from experimental results that the proposed measurement system is useful for acquiring magnetisation characteristics of the nanocrystalline alloy.